Design and fabrication of exhaust fan cleaner / Wan Amir Faisal Wan Adzmani - Wan Adzmani, Wan Amir Faisal (2022)
Exhaust fans are used to pull excess moisture and unwanted odours out of a particular room or area. They are commonly found in bathrooms and kitchens, where moisture can build up due to activities such as showering, washing, or cooking. The objective of this project is to build an exhaust fan with its own cleaning mechanism. Cleaning exhaust fan had always been a common thing as it will increase its efficiency when cleaned. The problem arise when the cleaning process occur and a lot of things had to be stop in order for the exhaust fan to be clean. Cleaning the exhaust fan also consume a lot of energy as the process for cleaning it have a lot of steps. The expectation from this project is to lessen the burden of workers with an exhaust fan that can clean itself and the cleaning process of the exhaust fan will not interfere with the workers works.